Analisis pengaruh beban siklis terhadap fatigue dan deformasi baling-baling drone menggunakan metode elemen hingga (Program Studi Teknik Mesin Fakultas Teknik Universitas Pasundan, 2026)
This study aims to analyze the fatigue and deformation of drone propellers made of carbon fiber using the Finite Element Method (FEM) through ANSYS simulation. The applied loads include the drone weight of 3.6 kg and additional loads of 0.5 kg and 0.75 kg, distributed evenly across six propellers. Simulation results indicate that the propellers’ fatigue life remains within a safe range, with a maximum time of approximately 107 s, although the propeller tips are critical areas with the lowest safety factor, indicating a higher risk of failure. The deformation distribution shows that the middle section of the propeller remains relatively safe under load, while the tips experience stress concentration due to combined loads and airflow interaction. This study provides a basis for reinforcing critical areas of the propeller design and recommends further research to evaluate the effects of propeller shape variations and more complex flight conditions. The results are expected to enhance the fatigue life and operational safety of carbon fiber drone propellers.